A penicillin- and metronidazole-resistant Clostridium botulinum strain responsible for an infant botulism case. (July 2016) - Mazuet, C.; Yoon, E.-J.; Boyer, S.; Pignier, S.; Blanc, T.; Doehring, I.; Meziane-Cherif, D.; Dumant-Forest, C.; Sautereau, J.; Legeay, C.; Bouvet, P.; Bouchier, C.; et al.
Abstract: The clinical course of a case of infant botulism was characterized by several relapses despite therapy with amoxicillin and metronidazole. Botulism was confirmed by identification of botulinum toxin and Clostridium botulinum in stools. A C. botulinum A2 strain resistant to penicillins and with heterogeneous resistance to metronidazole was isolated from stool samples up to 110 days after onset. Antibiotic susceptibility was tested by disc agar diffusion and MICs were determined by Etest. Whole genome sequencing allowed detection of a gene cluster composed of bla CBP for a novel penicillinase, blaI for a regulator, and blaR1 for a membrane-bound penicillin receptor in the chromosome of the C. botulinum isolate. The purified recombinant penicillinase was assayed. Resistance to β-lactams was in agreement with the kinetic parameters of the enzyme. In addition, the β-lactamase gene cluster was found in three C. botulinum genomes in databanks and in two of 62 genomes of our collection, all the strains belonging to group I C. botulinum . This is the first report of a C. botulinum isolate resistant to penicillins. This stresses the importance of antibiotic susceptibility testing for adequate therapy of botulism.